Pengaruh Working Capital Turnover dan Debt To Equity Ratio Terhadap Return On Assets Pada Pt.Kalbe Farma Tbk Dari Tahun 2003 – 2015 - Jerrey Rusli dan Yolanda (Fakultas Ekonomi Universitas Borobudur, 2017)
The purpose of this study was to determine the effect Working Capital Turnover and Debt to Equity Ratio of Return on Assets. By using quota sampling method of sampling using secondary data during the period 2003 to 2015, with the help of eviews analysis tool 9, using multiple linear regression method. The results of the study indicate where simultaneous variable Turnover Working Capital and Debt to Equity Ratio significant effect on Return on Assets. Partially show analysis1: Working Capital Turnover variable positive effect on Return on Assets. In analysis2: variable Debt to Equity Ratio negative effect on Return on Assets.